Le collier et la perle - Diallo, Mamadou Sellou (France, 2009)
"The Necklace and the Bead" is a letter from a father to his daughter, exploring the mystery of woman through many lenses - from the woman as a body of pain that gives life, to the woman’s body as an object of seduction, to the woman’s ever-mutilated body.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films